Cytokine release syndrome and successful response to pembrolizumab therapy in a patient with EGFR‐mutated non‐small‐cell lung cancer: A case report - Meng Zhang; Yuan Cheng; Yan Hu; Ligong Nie (Thoracic Cancer, 2022)
Abstract A therapeutic option for advanced non‐small‐cell lung cancer (NSCLC) patients with epidermal growth factor receptor (EGFR)‐tyrosine kinase inhibitor (TKI) resistance is a clinical challenge. The clinical outcomes of pembrolizumab in those patients is inconclusive. Cytokine release syndrome (CRS) is a rarely reported immune‐related adverse event in the field of immune checkpoint inhibitors therapy, raising challenges given the paucity of data with such presentations. We present the unique case of a 67‐year‐old female with advanced EGFR‐mutated NSCLC who successfully responded to pembrolizumab after EGFR‐TKI resistance. However, the patient developed CRS after pembrolizumab initiation and presented with fever, rash, hypotension, hypoxemia, tachycardia, and multiple organ dysfunction. Blood tests showed elevated levels of peripheral CD8+ T cells, C‐reactive protein, and tumor necrosis factor‐α. The symptoms rapidly improved after corticosteroid initiation. Based on the present case, we propose that pembrolizumab might be a potential salvage therapy for patients with advanced EGFR‐mutated NSCLC after EGFR‐TKI resistance; CRS would be a sign of the antitumor effect of PD‐1 inhibitors in those patients. However, CRS can be a fatal adverse effect and clinicians must remain vigilant for the rare toxicities to make prompt diagnosis and treatment.